Counselors’ Strategies in Addressing Students’ Learning Concentration Problems in the Digital Distraction Era: A Narrative Study - Gipa Gisnando; Eko Sujadi (Suluh: Jurnal Bimbingan dan Konseling, 2026)
Background: The rapid development of digital technology has increased distractions that negatively affect students’ concentration during learning. While previous studies have widely examined the impact of digital distraction on students’ academic performance, limited research has specifically explored school counselors’ professional experiences in addressing students’ concentration problems in digitally saturated learning environments. Aim; This study aims to explore school counselors' experiences in addressing students’ concentration problems in the era of digital distraction. The study employed a qualitative narrative approach, with data collected through in-depth interviews, non-participant observation, and documentation involving three school counselors at junior and senior high school levels in Kerinci Regency. Method: Data were analyzed using Riessman’s narrative analysis model. The findings reveal three interrelated themes. First, digital distractions such as smartphone notifications, online games, and social media are perceived as the primary sources of students’ concentration problems. Second, counselors emphasize strengthening students’ self-regulation through time management, control of digital device use, and mindfulness as central counseling strategies. Third, the sustainability of behavioral change in learning concentration depends on collaboration among counselors, teachers, and parents. This study contributes theoretically by enriching narrative counseling perspectives in understanding digital distraction as a systemic issue in school contexts. Practically, it provides experience-based strategic implications for school counseling interventions to improve students’ learning concentration in the digital era.